(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2019)
The article deals with some pragmatic parameters of Ukrainian-language culinary site as a special genre in the communicative space of Internet. It is a specific electronic dynamic cookbook existing in the socio-communicative situation of the transfer (dissemination) of experience. The communicative purpose of the culinary sites is through the selection and presentation of recipes relaying culinary experience, attracting a wide range of recipients to culinary art, forming a positive evaluative attitude to food and cooking as an important part of social and cultural life of the person. Authors of culinary sites are keen to encourage recipients to culinary experimentation, promote the idea of healthy homemade food and nutrition. The generalized images of a narrator (author) and narratee (recipient) of Ukrainian culinary sites are described. The typical author is not a professional cook or shef, but an experienced mistress who shares her experiences and secrets of home cooking, recipes of dishes, personally tested and proven. Home cooking is presented as an important factor in a happy family life, joy and pleasant emotions. It has been found that culinary sites are intended for a wide range of recipients, but the main target audience is women. There are two main groups of narratees. The first group contains experienced cooking lovers, amateur cooks tending to vary their daily meals, expand their culinary experience. The second one consists of novices, beginners who want to learn how to cook delicious dishes – quick and easy to prepare – at home.